Deposit Insurance and Wealth Effects: The Value of Being “Too Big to Fail” - O'HARA, MAUREEN; SHAW, WAYNE (Journal of Finance, 1990)
ABSTRACT This paper investigates the effect on bank equity values of the Comptroller of the Currency's announcement that some banks were “too big to fail” and that for those banks total deposit insurance would be provided. Using an event study methodology, we find positive wealth effects accruing to TBTF banks, with corresponding negative effects accruing to non‐included banks. We demonstrate that the magnitude of these effects differed with bank solvency and size. We also show that the policy to which the market reacted was that suggested by the Wall Street Journal and not that actually intended by the Comptroller.